Literasi Zakat Pertanian pada Masyarakat Desa - Tasriani Tasriani (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2021)
This study aims to determine the literacy of the village community about agricultural zakat and what factors are behind the lack of village people in paying agricultural zakat. This research approach uses a qualitative descriptive approach. Collecting data from this research are interviews, documentation, and observations. The sources of data obtained from primary data sources are from the head of Sidodadi Village, one of the hamlet heads, community leaders, and farmers. While the secondary data source is documentation obtained from the field. Zakat is a property that must be issued for Muslims to those who are entitled to receive it, such as the faqir, poor, amil, converts, slaves, gharim, fisabilillah, and ibn sabil. The agricultural zakat is all agricultural produce that is planted using seeds, the results of which can be eaten by humans and animals. Agricultural zakat can be in the form of grains, tubers, vegetables, fruits, flowers, and so on. The results of this study are the lack of public literacy about agricultural zakat, besides that there has been no socialization about agricultural zakat from community leaders and from the government which causes the people of Sidodadi Village to have low agricultural zakat literacy.